Science in Underground Laboratories and DULIA-Bio - Ianni, Aldo (Frontiers in Physics, 2021)
This paper reports a brief introduction to Deep Underground Laboratories (DULs) and the connection they have with research on biology in extreme environments and the effect of radiation in life. Presently, there are 14 DULs in operation worldwide. Although the main research activity in these infrastructures concerns the search for rare events in astroparticle physics and neutrino physics, DULs offer a unique opportunity to undertake experiments in astrobiology and biology in extreme environments. This is the main motivation of Deep Underground Laboratory Integrated Activity in biology (DULIA-bio) 2019 Workshop, which was held at the Gran Sasso (Italy) underground laboratory. This paper aims to give an introduction to the subject of the Workshop by reviewing the main features of DULs.